(The Effects of Drying on Rehidration Coefficient, Shear and Rendement of Mushroom) - Alamsyah, Rizal; Mahdar, Putiati; Syah, Ishak (Balai Besar Industri Agro, 1997)
Data relating to physical properties and characteristic of dried mushroom was very useful information especially for packaging, storage, and transportation purposes. The objectives of this study were to investigate some physical characteristics covering, rehidration coefficient, shear stress, as well as rendement of mushroom affected by drying. The drying experiment were conducted at 4 level temperature (35 derajat celcius, 40 derajat celcius, 45 derajat celcius and 50 derajat celcius), and level 4 drying air speed (1 m/sec, 1.5 m/sec, 2.0 m/sec, and 2.5 m/sec) with and without blanching treatment. Dried mushroom with blanchead treatment gave better rendement (aximum 12,67%) and shear stress value (maximum 18954,00 Newton/m2) comparing with those without blanched treatment. In the other hand dried mushroom with blanched treatment showed better appearance and rehiration coefficient (maximum 4,31) than those without blanched treatment.